2013
DOI: 10.1111/gwao.12004
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐Making Factors within Paternity and Parental Leaves: Why Spanish Fathers Take Time Off from Work

Abstract: This article aims to understand how Spanish fathers construct and justify their decisions to use both paternity and parental leaves. Specifically, we analyse the fathers' discourse about paid work conditions, the couple's decision‐making process, formal and informal care resources, and care and gender equality. We divided responders according to the type of leave that they took and the length of time away from work; as a result, participants in this study were placed into three groups: (1) fathers who take 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 27 publications
3
28
0
4
Order By: Relevance
“…No statistically significant differences were observed among women in this respect. These findings were consistent with earlier qualitative studies according to which the discourse characteristic of men using parental leave was more family-and childcare-than career-oriented (Romero- Balsas et al, 2013, Muntanyola-Saura, RogeroGarcía, 2013Brandth and Kvande, 2002).…”
Section: Reasons For Taking Parental Leavesupporting
confidence: 92%
See 1 more Smart Citation
“…No statistically significant differences were observed among women in this respect. These findings were consistent with earlier qualitative studies according to which the discourse characteristic of men using parental leave was more family-and childcare-than career-oriented (Romero- Balsas et al, 2013, Muntanyola-Saura, RogeroGarcía, 2013Brandth and Kvande, 2002).…”
Section: Reasons For Taking Parental Leavesupporting
confidence: 92%
“…Particular research has addressed paternity leave (Romero-Balsas, 2012;Flaquer and Escobedo, 2014;Escot et al, 2014, Fernández-Cornejo andPoza, 2014;Meil, 2017), unpaid full-time parental leave (Lapuerta, Baizán and González, 2011;Romero-Balsas et al, 2013, Muntanyola-Saura andRogero-García, 2013), part-time parental leave (Lapuerta et al, 2011) and men's use of maternal leave (Escot et al, 2012, Fernández-Cornejo, Lafuente andPoza, 2012;Meil et al, 2017b, Romero-Balsas andRogero-García, 2017b). In this article, in keeping with the international literature on the subject, leave of absence (excedencia por cuidado de hijos) and part-time parental leave or reduced hours (reducción de jornada por cuidado de hijos) are referred to as parental leave.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, algunos trabajos señalan también la diversidad de prác-ticas y representaciones existente entre grupos sociales sobre aquello que es y debe ser la implicación paterna. Asimismo, se identifican resistencias, socio-institucionales e ideológicas, al desarrollo de lo que la literatura llama una paternidad (co)responsable (Barbeta-Viñas y Cano, 2017;González y Jurado, 2015;Romero-Balsas, et al, 2013).…”
Section: Acercamiento Al Análisis De La Implicación Paternaunclassified
“…Remuneration (whether and to what extent leave is paid) is a determinant in this respect. That most fathers take paternity leave (Flaquer and Escobedo 2014 ;Romero-Balsas et al 2013 ), during which they are paid 100 % of their salaries, stands as confi rmation. Nonetheless, in a study on full-time parental leave based on data for 2006, Lapuerta ( 2013 ) found a higher take-up rate among women in Spanish regions where some manner of remuneration was in place (salary-related in most cases) than where none existed, but observed no signifi cant differences for men.…”
Section: Factors Encouraging Men To Take Leave Alonementioning
confidence: 99%